Srpski - Zalad, Gordana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
This paper is a contrastive genre study of political discourse in newsmagazines in two different political, social, cultural and language contexts. The research object of the study is rhetorical and language analysis in the newsmagazines (Time and Nin) with a „common platform“ of subject matter on Kosovo, taking into account its importance and the number of texts devoted to Kosovo in both magazines. The theoretical framework consists of: new contrastive rhetoric; new rhetoric genre studies; critical discourse analysis and systemic functional linguistics. The research has been conducted on a corpus collection of 50 articles in English and Serbian languages, during the period of 2000-2013, published in two newsmagazines at different level of circulation. The main assumption in the genre theory that genre is a social action has been applied in this study in the sense that the articles of newsmagazines represent social activity in the institutional context in two different settings. The micro-genre analysis has shown significant difference in the two sets of articles: the most dominant micro-genre in the English corpus is argumentative media exposition, while explanatory media exposition is in the Serbian corpus. Deep rhetorical analysis of the data has shown significant differences in the structure of the texts. The authors of Serbian articles have shown greater individuality and diversity in the formation of their commentaries